Uvite, CaMg3(Al5Mg)(Si6O18)(BO3)3(OH)3(OH), a new, but long-anticipated mineral species of the tourmaline supergroup from San Piero in Campo, Elba Island, Italy. (31st October 2022) - Bosi, Ferdinando; Biagioni, Cristian; Pezzotta, Federico; Skogby, Henrik; Hålenius, Ulf; Cempírek, Jan; Hawthorne, Frank C.; Lussier, Aaron J.; Abdu, Yassir A.; Day, Maxwell C.; Fayek, Mostafa; Clark, Christine M.; et al.
Abstract: Uvite, CaMg3 (Al5 Mg)(Si6 O18 )(BO3 )3 (OH)3 (OH), is a new mineral of the tourmaline supergroup. It occurs in the Facciatoia quarry, San Piero in Campo, Elba Island, Italy (42°45′04.55″N, 10°12′50.89″E) at the centre of a narrow (2–3 cm wide) vein composed of aggregates of dark brown to black tourmaline, penetrating (magnesite + dolomite)-rich hydrothermally altered metaserpentinite. Crystals are euhedral and up to 1 cm in size, brown with a vitreous lustre, conchoidal fracture and grey streak. Uvite has a Mohs hardness of ~7½, a calculated density of 3.115 g/cm 3 and is uniaxial (–). Uvite has trigonal symmetry, space group R 3 m, a = 15.9519(10) Å, c = 7.2222(5) Å, V = 1597.3(1) Å 3 and Z = 3. The crystal structure was refined to R 1 = 1.77% using 1666 unique reflections collected with Mo K α X-rays. Crystal-chemical analysis resulted in the empirical crystal-chemical formula $^X ({\rm Ca}_{0.61}{\rm Na}_{{0.35}} \square_{{0.04}})_{\Sigma 1.00}{}^{Y} \left( {{\rm Mg}_{1.50}{\rm Fe}^{2 + }_{0.47} {\rm Al}_{0.71}{\rm Fe}^{3 + }_{0.14} {\rm Ti}_{0.18}} \right)_{\Sigma 3.00}$ ${}^{Z} \left( {{\rm Al}_{4.54}{\rm Fe}^{3 + }_{0.18} {\rm V}^{3 + }_{0.02} {\rm Mg}_{1.27}} \right)_{\Sigma 6.00}{}^{T}\left[ {{\left( {{\rm Si}_{5.90}{\rm Al}_{0.10}} \right)}_{\Sigma 6.00}{\rm O}_{18}} \right]{\rm } \left( {\rm BO_3} \right)_3^{} {^{\rm O(3)}}\left( {\rm OH} \right)_3{}^{{\rm O}\left( 1 \right)} [\left( {\rm OH} \right)_{0.55}{\rm F}_{0.05}{\rm O}_{0.40}]_{\Sigma 1.00}$ which recast in its ordered form for classification purposes is: $$\eqalign{& ^{\rm X} ({\rm Ca}_{0.61}{\rm Na}_{0.35}\squ _{0.04})_{\Sigma 1.00}{}^{\rm Y} \left( {{\rm Mg}_{2.35}{\rm Fe}^{2 + }_{0.47} {\rm Ti}_{0.18}} \right)_{\Sigma 3.00} \cr & {}^{\rm Z} \left( {{\rm Al}_{5.25}{\rm Fe}^{3 + }_{0.32} {\rm V}^{3 + }_{0.02} {\rm Mg}_{0.42}} \right)_{\Sigma 6.00}{}^{\rm T} \left[ {{\left( {{\rm Si}_{5.90}{\rm Al}_{0.10}} \right)}_{\Sigma 6.00}{\rm O}_{18}} \right]{\rm }\left( {\rm BO_3} \right)_3{}^{\rm V} \left( {\rm OH} \right)_3{}^{\rm W} [\left( {\rm OH} \right)_{0.55}{\rm F}_{0.05}{\rm O}_{0.40}]_{\Sigma 1.00}}$$ Uvite is a hydroxy-species belonging to the calcic-group of the tourmaline supergroup. The closest end-member compositions of valid tourmaline species are fluor-uvite and feruvite, to which uvite is related by the substitutions W (OH) – ↔ W F – and Y Mg 2+ ↔ Y Fe 2+, respectively. The occurrence of a solid-solution between uvite and magnesio-lucchesiite, according to the substitution Z Mg 2+ + W (OH) – ↔ Z Al 3+ + W O 2–, is supported by experimental data. The new mineral was approved by the IMA–CNMNC (IMA 2019-113). Uvite from Facciatoia formed by the reaction between B-rich fluids, released during the crystallisation process of LCT pegmatites, and the surrounding metaserpentinites, altered by contact metamorphism in the aureole of the Miocene Mt. Capanne monzogranitic pluton.